Do our medical undergraduates need to develop research skills? Assessing perceptions, attitudes and skills of medical undergraduates - Patel, Neha A. (International Journal Of Community Medicine And Public Health, 2019)
Background: The development of research capacity at undergraduate level is essential to produce good quality researchers in the long run. The core curriculum must ensure that relevant and appropriate research expertise is attained by all graduates who are then provided with a suitable foundation from which they can develop such specialized research skills as may be required in their careers. Methods: A cross sectional study was conducted in Terna Medical College, Nerul, Navi Mumbai from May 2016- September 2016. All students of second and third year who willingly participated were included in the study. Preformed pretested and validated proforma was used. For checking attitudes a standard attitudes towards research scale was been used which contained 32 questions. Results: 74.9% said that research methodology should be the part of curriculum. 37.7% said that they would like to opt a carrier as a researcher. 70.6% students either identified no opportunities, gave no response or didn’t know about opportunities. Biggest barriers identified were lack of knowledge (36.5%), lack of time (34.7%), lack of infrastructure (25.1%). Correlation coefficients between ATR sub-scales were also calculated. Conclusions: Students’ want to conduct research at undergraduate level and want incorporation of research methodology in curriculum. Lack of knowledge, time and resources are common barriers while opportunities, majority are not aware about it. Though students find research difficult and are anxious about it, they have positive attitude towards conducting research.